3‐D low numerical dispersion WLP‐FDTD method with artificial anisotropy parameters. Issue 5 (14th December 2021) - Liu, Gui‐Ying; Ma, Ping; Tian, Jing; Quan, Jun; Chen, Wei‐Jun
Abstract: Based on the weighted Laguerre polynomials (WLPs) and artificial anisotropic (AA) parameters, a 3‐D unconditionally stable finite‐difference time‐domain (FDTD) electromagnetic simulation approach is proposed. The implementation of WLPs in time domain effectively eliminates the time step and AA parameters in spatial difference, resulting in suppressed numerical dispersion error. The monochromatic wave is employed as an example to obtain the numerical dispersion relationship of 3‐D AA‐WLP‐FDTD under AA parameter, in which reduced numerical dispersion error is observed. Compared with the conventional WLP‐FDTD technique, this approach demonstrates smaller numerical dispersion error under similar calculation cost.